Food and Nutrition Security in Urban Slums: Consumer Survey data for Kenya and Uganda - Onyango, Kevin Omondi; Chege, Christine Gacheri Kiria; Jager, Matthias; Karanja, David; Nkalubo, Stanley T. (2023)
This paper presents data collected in July 2016 to assess the consumption patterns and dietary quality among vulnerable urban consumers at the Base of Pyramid (BoP). The data was collected within the project ‘Making Value Chains Work for Food and Nutrition Security of Vulnerable Populations in East Africa’ which was funded by the German Federal Ministry for Economic Cooperation and Development (BMZ). The project was led by the Alliance of Bioversity and CIAT and implemented in partnership with KALRO, NARO, Goettingen University and UHOH. The project was under the CGIAR flagship program “Food Systems for Healthier Diets” under the Research Program on Agriculture for Nutrition and Health (A4NH).